PENGARUH PENGGUNAAN MEDIA INTERAKTIF BERBASIS POWERPOINT TERHADAP MOTIVASI BELAJAR IPAS KELAS V SD NEGERI 040446 KABANJAHE - Eti Muliani; Nurlia Ginting; Agustriani Br Simbolon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using interactive PowerPoint media on the learning motivation of fifth-grade students at SD Negeri 040446 Kabanjahe in the 2025/2026 academic year. The research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research subjects consisted of two classes: Class V A as the experimental group and Class V B as the control group, with a total of 54 students. The experimental class received instruction using interactive PowerPoint media, while the control class was taught using conventional learning methods. The research instrument was a learning motivation questionnaire that had been tested for validity and reliability. Data collection was conducted through pretest and posttest administrations in both groups. The collected data were analyzed using descriptive and inferential statistics with the assistance of SPSS software. The prerequisite tests included normality and homogeneity tests, while hypothesis testing was conducted using an independent samples t-test. The results showed that the average learning motivation score of students in the experimental class increased more significantly than that of the control class. Based on the hypothesis testing results, the significance value was less than 0.05, indicating that the alternative hypothesis was accepted. Therefore, it can be concluded that the use of interactive PowerPoint media has a significant effect on students’ learning motivation. Interactive PowerPoint media effectively enhances students’ interest, attention, and active participation in the learning process.